“One nation, one god, one state”: The relationship between religious practice and national identity in Croatia and Serbia - Penić, Sandra; Spini, Dario; Jelić, Margareta (2012)
Following the violent dissolution of former Yugoslavia, religious organizations played an important role in rebuilding the nation-states in Croatia and Serbia. The number of religious persons rose dramatically, and religious identities became intertwined with national identities. Critics of religious organizations in former Yugoslavia, however, stress their role as co-engineers of crisis and conflict and promoters of xenophobic and exclusionary nationalism. In this research, we examine the impact of religious practice on both national attachment and xenophobic national glorification. The results of multi-level analyses on a representative cohort sample from 34 areas of Croatia and Serbia show that, on a contextual level, living in an area where religion is strongly practiced is not related to stronger feelings of general national attachment. Yet it is a crucial predictor of national glorification and the exclusion of conflict group members. These findings are then complemented by a discourse analysis of the official Catholic Church’s weekly journal in Croatia from 1986 to 2006. These analyses help clarify what constitutes a Croatian national identity (i.e. the boundaries, norms and prototypes), as promoted by the Church. By examining the content of articles over a 20-year time period, one marked by dramatic structural and political changes, we illustrate how certain interpretations of past and present critical collective events are rhetorically constructed in order to promote a particular version of national belonging and disqualify competing ones. Overall, our findings emphasize the importance of studying not only the intensity but also the content of national identities. They further lend insight into the mechanisms by which “entrepreneurs of identity” mobilise people towards accepting particular meanings of national belonging.
ENG